Hydrodynamics of bubble column reactors at high gas velocity: experiments and computational fluid dynamics (CFD) Simulations - Rampure, Mohan R.; Kulkarni, Amol A.; Ranade, Vivek V. (Industrial & Engineering Chemistry Research, 2007)
This paper focuses on the modeling of flow and mixing in a bubble column reactor operated at high gas velocities (up to 0.40 m/s). A dual-tip conductivity probe was used to measure local void properties such as local time-averaged gas holdup, chord length distribution, bubble velocity distribution, and interfacial area. Chord length distribution was converted to bubble size distribution, using the backward transformation method. Liquid-phase mixing time measurements were conducted using a conductivity probe. A computational fluid dynamics (CFD) model was developed to simulate the unsteady gas-liquid flow in a bubble column using commercial code FLUENT 6.2. The time-averaged flow properties predicted by CFD simulations were compared with the experimental data. The role of unsteady flow structures in mixing was studied. The `' multiple snapshots `' approach was used to simulate the mixing time using CFD. The mixing times that were predicted for all superficial gas velocities compared favorably to the measured values. This study of the hydrodynamic behavior of a bubble column at higher gas velocity provides a basis for understanding and simulating solid suspension (or solid mixing) in slurry bubble column reactors.

Modeling of bubble column slurry reactor for reductive alkylation of p-phenylenediamine - Chaudhari, Amit S.; Rampure, Mohan R.; Ranade, Vivek V.; Jaganathan, Rengaswamy; Chaudhari, Raghunath V. (Chemical Engineering Science, 2007)
A bubble column slurry reactor (BCSR) model has been developed for the reductive alkylation of p-phenylenediamine (PPDA) with methyl ethyl ketone (MEK) to N, N'-di-secondary-alkyl-p-phenylenediamine (Di-amine). This particular reaction system is commercially relevant and involves a combination of parallel and consecutive reactions comprising equilibrium non-catalytic (homogeneous) and catalytic (heterogeneous) steps. The proposed model is based on the `mixing cell approach'. In this work the mixing cell approach has been extended by including a liquid backflow stream from all but the bottommost mixing cell. The model incorporates the contributions of gas-liquid and liquid-solid mass transfer, heat effects, and complex multistep reaction kinetics. CFD model is used to estimate the extent of backflow among mixing cells and its dependence on operating parameters. The effect of gas and liquid velocities, catalyst loading, inlet PPDA concentration, and temperature on the conversion, selectivity, global rate of hydrogenation, and temperature rise is discussed. The comparison of the current approach with the traditional mixing cell model is discussed. The BCSR model presented here will be useful to provide guidelines for designing and improving overall performance of bubble column reactors. (C) 2007 Elsevier Ltd. All rights reserved.
Keywords: bubble columns; CFD; kinetics; Mathematical modeling; Reductive alkylation